Remains of the day - Ishiguro, Kazuo 1954- (London Faber & Faber, 1989)
Compelling story of a man torn between what he wants to believe and what he knows to be true. Stevens, for three decades a butler to the late Lord Darlington, reluctantly takes a rare holiday to visit the former housekeeper, Miss Kenton. His visit stirs up disturbing memories of their troubled relationship. Stevens' peace is further shaken by recollections that cast new light on his late employer's politics on the eve of World War II.
Abridged.
In container (18 cm.).
Read by Michael York.
Keywords: Butlers -- Fiction; England -- Fiction; Historical fiction; Love stories